Penerapan Fungsi Perencanaan Dakwah dalam Meningkatkan Kualitas Organisasi Majelis Taklim - Wulandari, Santi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Planning is a core part of the management function to achieve certain goals. The Nurul Falah Taklim Council has a plan that forms the basis for improving its quality, so that the planning carried out at the taklim assembly can be directed, achieve goals, and can be accounted for, so that a planning concept is needed to guide and underlie every activity carried out. The purpose of this research is to find out how forecasting, goal setting, programming, scheduling and budgeting of the Taklim Nurul Falah Council are. The research method used is descriptive method with a qualitative approach. Based on the results of the research, it shows that the process of implementing planning carried out by the Nurul Falah Taklim Council in improving its quality includes: First, forecasting, namely forming management for a term of one term of one period of five years, and planning activity programs. Second, determining the main objectives of the taklim assembly with the hope of carrying it out and providing religious education to educate and form an Islamic society. Third, activity programming is divided into two based on long and short term. Fourth, scheduling weekly and annual activities. Fifth, the budgeting for the costs of the taklim assembly comes from the congregation's weekly infaq cash.